Physical Activity In Young University. Descriptive Study 2022-2023 - Amador Rodero, Eulalia María (2026)
Introducción: Despite the importance of physical activity, there is an increasingly growing tendency to abandon this important practice in healthy lifestyles, in the transition that individuals make from adolescence to adulthood represented in the transition of school to university. Objective: To characterize physical activity practices in a group of university students. Methods: Cross-sectional descriptive-analytical study in a sample of 544 university students from different cities. The analysis of the lifestyle and physical activity variables was carried out by applying the Lifestyle Questionnaire in Young University Students (CEVJU-R2) with a Cronbach’s alpha of 0.67. Results: 57% of the population were women, the minimum age was 16 years and the maximum age was more than 25. Regarding physical activity practices, 63% do not carry out active movements. 41% never practice any sport for competitive purposes p-value 0.0001 and 15% never exercise for 30 minutes at least three times a week p-value 0.0258. Conclusions: despite the importance of PA as a strategy for the control of chronic non-communicable diseases, the preservation of health in general, in the population studied a tendency to stop PA was evident, favoring a sedentary lifestyle, this associated with academic responsibilities in the university environment and personal perception of safety and personal care.